2021
DOI: 10.3390/ijerph182212080
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID-19 Pandemic on Family Mental Health in Canada: Findings from a Multi-Round Cross-Sectional Study

Abstract: Pandemic-related disruptions, including school, child care, and workplace closures, financial stressors, and relationship challenges, present unique risks to families’ mental health. We examined the mental health impacts of the coronavirus disease 2019 (COVID-19) pandemic among parents with children <18 years old living at home over three study rounds in May 2020 (n = 618), September 2020 (n = 804), and January 2021 (n = 602). Data were collected using a cross-sectional online survey of adults living in Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…The level and change of income can affect people’s state of depression, anxiety, sleep, interpersonal relationships, etc. [ 26 , 27 , 28 , 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The level and change of income can affect people’s state of depression, anxiety, sleep, interpersonal relationships, etc. [ 26 , 27 , 28 , 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, lower income brings huge economic pressure, which makes individuals face more psychological crises, showing psychological symptoms such as anxiety, loneliness, and sensitivity to human relationships. On the other hand, higher income increases people’s financial ability to afford a spending budget for the living standards and professional services that are required to maintain healthy lifestyles, improving factors such as depression, impaired relationships, and food security [ 26 , 27 , 28 , 29 , 47 ]. However, existing research shows that for low-income groups and middle- and high-income groups, the impact of income changes on their mental health may be different [ 39 ], and this group difference shows that income has a non-linear effect on mental health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another feature of current research is apt to prove that there is a positive correlation between income and mental health. For instant, most scholars ( Ao et al, 2020 ; Thomson et al, 2020 ; Liang et al, 2021 ) believe that income has a positive impact on mental health during COVID-19. However, due to the obvious endogeneity between income and mental health, it is difficult to obtain consistent estimates by OLS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower income can bring huge economic pressure to person’s life, which may makes individuals face more psychological crises, showing psychological symptoms such as anxiety, loneliness, and sensitivity to human relationships. On the other hand, higher income increases people’s financial ability to afford a better budget for the higher living standards and professional services for maintaining healthy lifestyles, improving factors such as depression, impaired relationships, and food security ( Ao et al, 2020 ; Thomson et al, 2020 ; Xiao et al, 2020 ; Liang et al, 2021 ; Jiang et al, 2022 ). Based on the above analysis, we propose Hypothesis 1.…”
Section: Introductionmentioning
confidence: 99%
“…In China [18], reported that women endorsed higher levels of hyperarousal, difficulty sleeping, and negative reactions or moods, symptoms commonly associated with posttraumatic stress disorder. Several studies proposed that the disproportionate number of women experiencing "high stress" is potentially attributable to women being more likely to work in high-risk environments, such as clinics, or as a function of their status as primary caregivers to children, significant others, or parental figures [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%